Heat Transfer Evaluation in MgZn6Zr/C8H18 [(Magnesium–Zinc–Zirconium)/Engine Oil] With Non-linear Solar Thermal Radiations and Modified Slip Boundaries Over a 3-Dimensional Convectively Heated Surface - Adnan; Khan, Umar; Ahmed, Naveed; Khan, Ilyas; Mohamed, Abdullah; Mehrez, Sadok (Frontiers in Energy Research, 2022)
This analysis is concerned about the thermal performance of [(MgZn6Zr)/C8H18]nf by incorporating the essential concept of non-linear thermal radiations. The flow is configured over a 3D stretchable surface which is heated convectively and the surface boundaries updated with slip effects; uniform suction is applied. The proper mathematical modeling is performed by exercising the nanofluids’ empirical correlations and similarity equations. Thereafter, the RK scheme is utilized to execute the problem solution. The influences of imperative flow constraints are furnished and discussed deeply. The results revealed that [(MgZn6Zr)/C8H18]nf motion decays against suction (R1) and slip effects (γ1). The investigation of the results disclosed that the induction of non-linear thermal radiations in the model boosted the internal energy of the fluid, and hence, the nanofluid thermal efficiency improved. Moreover, convection provided from the surface (Bi number) was also of paramount interest regarding the heat transport in [(MgZn6Zr)/C8H18]nf. Furthermore, significant contribution of the temperature ratio parameter βw is examined in thermal enhancement. Optimum shear stress trends are investigated due to suction from the surface. Finally, we hoped that the problem would be beneficial in the field of applied thermal engineering, more specifically in the heat transport models.